Beyond the organisational accident: the need for "error wisdom" on the frontline - Reason, J (BMJ Group, 2004)
Complex, well defended, high technology systems are subject to rare but usually catastrophic organisational accidents in which a variety of contributing factors combine to breach the many barriers and safeguards. To the extent that healthcare institutions share these properties, they too are subject to organisational accidents. A detailed case study of such an accident is described. However, it is important to recognise that health care possesses a number of characteristics that set it apart from other hazardous domains. These include the diversity of activity and equipment, a high degree of uncertainty, the vulnerability of patients, and a one to one or few to one mode of delivery. Those in direct contact with patients, particularly nurses and junior doctors, often have little opportunity to reform the system's defences. It is argued that some organisational accident sequences could be thwarted at the last minute if those on the frontline had acquired some degree of error wisdom. Some mental skills are outlined that could alert junior doctors and nurses to situations likely to promote damaging errors.